Pengembangan LKPD Pemodelan Matematika Siswa SMP Menggunakan Konteks Ojek Online - Saputri, Nety Wahyu; Zulkardi (Mathematics Education Journal, 2020)
The aim of this research is to generate LKPD (student worksheet) that is valid, practical, and has potential effects on student’s proficiency to create mathematical modeling. The research based on the fact that students’understanding and ability to engage mathematical concepts and real world problems in order to solve them are inadequate. Therefore, mathematical modeling is employed to assist students solve mathematical real world problem. Online Ojek is utilized as the context for student worksheet and the queries are given by adopting mathematical modeling phase. This study is a design research type of development study. The qualities of developed product shall support the progress of students in understanding problems, formulating mathematical models, and solving real world problem systematically applying Blum’s theory of mathematical modeling phase and PMRI characteristics. The subjects were 25 junior high school students from grade VII in Palembang. The results suggest that student worksheet fulfils validity indicator based on validators’ evaluation, practicality as evaluated from small group phase, and possess potential effects as assessed from students’ test results that were handed by the field test phase. The test results showed that 72% of students were categorized as good towards the ability of mathematical modeling after using the developed student worksheet.